Ambivalensie in die verhouding tussen slaaf en meester in Philida deur André P. Brink - Bothma, Mathilda (Tydskrif vir Letterkunde, 2015)
This article appropriates the views of critics in an effort to come closer to an understanding of the sensations, experiences and the general plight of slaves in a (post)-colonial context, in particular the farm Zandvliet, as well as the broader South-African society as represented in Philida. In this regard, for instance, the critical enunciations of Bill Ashcroft concerning place and displacement and the bearing thereof on the lives of the colonised is considered, as well as the views of Homi Bhabha on ambivalence related to colonial discourse. According to Bhabha the “other” is the coloniser’s construct and his relationship with the “other” is characterised by ambivalence and inconsistency. The article refers to the intertextual relations of Philida to earlier Brink novels, to the paratextual relations of the cover to the text, and to the text’s relations to South African history.